Analysis of Excessive Self-Defense (Noodweerexces) in the Crime of Persecution - Ines Adania Yusuf (Indonesian Research Journal in Legal Studies, 2025)
This study aims to examine and analyze the justification for excessive self-defense (noodweerexces) under the Criminal Code and to analyze court decisions granting release from all charges (ontslag van alle rechtsvervolging) in cases of persecution resulting from excessive self-defense. This research is classified as normative legal research, encompassing studies on legal principles, legal systematics, legal synchronization, legal history, and legal comparisons. The results of this study indicate that self-defense in persecution cases can be accepted as a justification that eliminates the perpetrator’s criminal liability. The removal of criminal liability in such cases serves as a form of legal protection against an immediate threat to the perpetrator’s honor and safety and recognizes the legitimacy of actions taken in response to imminent threats. It is suggested that although persecution may be committed as an act of self-defense, every act of self-defense must involve an immediate threat faced by the perpetrator, and the threat must endanger the perpetrator’s honor or safety. Furthermore, judges must consider the circumstances of both the perpetrator and the victim, ensuring that decisions to release the perpetrator from prosecution are rational and proportional, serving as legitimate justification for the elimination of criminal liability.